Effects of the environmental, occupational safety and health regulations towards the successful completion of a project / Susie Nadya Anak David Asen - Anak David Asen, Susie Nadya (2007)
A successful project normally depends on the ability to finish within the scheduled time and allocated budget. Contractors are also very keen to ensure that it satisfies the needs of the clients. Fulfilling these three elements which they often see as the key performance to obtain success and the maximum profit, they tend to forget two basic elements which are the environmental factor and the safety and health factor. Most construction companies seem to avoid these two elements since their contribution towards a project could be seen very insignificant. However, for long term success, both elements are in fact very significant. Therefore, the government has set the regulations in order to be obliged by the construction companies. For instance, the Environmental Quality Act 1974 (Act 127) and the Environmental Impact Assessment (EIA) are tools used to assess the overall impact on the environment of the development projects. As for the safety and health management, the performance of the construction project should always be monitored to reduce the statistics of accidents at construction site. Therefore, the Occupational Safety and Health Act 1994 (Act 514) was implemented by the Department of Safety and Health. This study was carried out by distributing questionnaires to construction companies around Penang, especially Seberang Perai, Kepala Batas, Bukit Mertajam and Georgetown. The purpose of the survey was to identify and determine the most significant effect of the environmental, occupational safety and health regulations towards the success of project based on the respondent’s experience in the industry. Main focus to respond is those with technical background and has been involved in the industry. From the data analysis by the SPSS program, the findings of the study showed that most construction companies agreed that both the regulations are very essential in achieving a quality product. However due to some constraint in complying with the requirements, they tend to neglect or put it as the least priority in their project target list.